A new approach in group decision-making based on pairwise comparisons. (2015) - Azadfallah, Mohammad; Azizi, Majid
A review of the supplier selection literature shows that the analytic hierarchy process (AHP) method is one of the most commonly applied methods in practice. However, a major drawback in applying AHP is that the required comparisons rises quadratically with the entities to be compared. In this paper, to resolve this limitation, a new approach is proposed. In the proposed model, the following ways for deriving priorities are suggested: i) decomposition of matrix method; ii) the geometric mean method. The finding in this paper shows that decomposing matrix method results are more reliable than others.